Serum thyroid hormones levels are significantly decreased in septic neonates with poor outcome - Kurt, A.; Aygun, A. D.; Sengul, I.; Sen, Y.; Kurt, A. N. Citak; Ustundag, B. (Springer, 2011)
The aim of this prospective study was to investigate the effects of thyroid hormone levels on the sepsis criteria and mortality in septic newborns. This study was performed at the Firat University Hospital Neonatal Intensive Care Unit. A group of septic newborns and a control group of healthy non-infected newborns were evaluated. Blood samples were obtained at onset from septic and healthy newborns and at 10(th) day of the antibiotic therapy from only septic newborns, and thereafter serum total T-3 (TT3), total T-4 (TT4), and TSH levels were determined. A total of 292 newborns were included in the study. Serum TT3 levels at onset and at 10(th) day of the antibiotic therapy were 163.8 +/- 63.4 and 178.3 +/- 33.1 ng/dl, TT4 levels were 6.9 +/- 2.2 and 11.0 +/- 2.6 mg/ml, and TSH levels were 3.8 +/- 2.1 and 4.0 +/- 2.5 mu U/ml, respectively in septic newborns. Serum TT3 levels were 180.3 +/- 47.6 ng/dl, TT4 levels were 10.9 +/- 2.3 mg/ml, and TSH levels were 4.1 +/- 2.2 mu U/ml in healthy newborns. Serum TT3, TT4 levels of septic newborns were significantly decreased with respect to those of healthy newborns at onset and serum TT4 levels was increased significantly after antibiotic therapy. To the best of our knowledge, this report is the first study to compare thyroid hormone levels in a large number of septic newborns and a healthy group. Our findings suggest that before and after treatment of neonatal sepsis a significant change is realized in thyroid hormone levels. (J. Endocrinol. Invest. 34: e92-e96, 2011) (C)2011, Editrice Kurtis
Keywords: Mortality; outcome; septic neonate; thyroid hormones